Thymus Species from Romanian Spontaneous Flora as Promising Source of Phenolic Secondary Metabolites with Health-Related Benefits - Mihai Babotă; Oleg Frumuzachi; Alexandru Nicolescu; Maria Inês Dias; José Pinela; Lillian Barros; Mikel Añibarro-Ortega; Dejan Stojković; Tamara Carević; Andrei Mocan; Víctor López; Gianina Crișan (MDPI AG, 2023)
Wild thyme aerial parts (Serpylli herba) are recognized as a valuable herbal product with antioxidant, anti-inflammatory, and antibacterial effects. Although pharmacopoeial regulations allow its collection exclusively from Thymus serpyllum, substitution with other species is frequent in current practice. This study analyzed the phenolic composition, antioxidant, and enzyme-inhibitory and antimicrobial activity of the hydroethanolic extracts obtained from five Romanian wild thyme species (Thymus alpestris, T. glabrescens, T. panonicus, T. pulcherimus and T. pulegioides). The analysis of individual phenolic constituents was performed through LC-ESI-DAD/MS2, while for the in vitro evaluation of antioxidant potential, TEAC, FRAP, DPPH, TBARS and OxHLIA assays were employed. The anti-enzymatic potential was tested in vitro against tyrosinase, α-glucosidase and acetylcholinesterase. High rosmarinic acid contents were quantified in all species (20.06 ± 0.32-80.49 ± 0.001 mg/g dry extract); phenolic acids derivatives (including salvianolic acids) were confirmed as the principal metabolites of T. alpestris and T. glabrescens, while eriodictyol-O-di-hexoside was found exclusively in T. alpestris. All species showed strong antioxidant potential and moderate anti-enzymatic effect against α-glucosidase and acetylcholinesterase, showing no anti-tyrosinase activity. This is the first detailed report on the chemical and biological profile of T. alpestris collected from Romanian spontaneous flora.